2011
DOI: 10.1080/00222348.2011.609782
|View full text |Cite
|
Sign up to set email alerts
|

Sonochemical Compatibility of Polyvinyl Alcohol/Polyacrylic Acid Blend in Aqueous Solution

Abstract: Ultrasonic velocities, viscosities, and densities of polyvinyl alcohol (PVA), polyacrylic acid (PA), and their mixtures (1:1 and 1:2) in aqueous solutions were measured. Various acoustic parameters were calculated as a function of concentrations of PVA, PA, and PVA-PA mixtures in water with the resonance method at ultrasound frequencies of 2, 3, 5, and 10 MHz at 30 • C. From the comparative results, the mode of interactions of the two polymers was shown to be due to hydrogen bonding. The bonding among the hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…The apparent viscosities of the EG01, EG13, EG11, EG31, and EG10 solutions were 2.51, 6.74, 5.24, 13.40, and 8.53 Pa s, respectively. When the weight ratio of ethylcellulose content was less than 50%, the viscosity of the blend was higher than that of the gelatin solution and lower than that of the ethylcellulose solution, indicating good compatibility on blending . Further, a minimum viscosity was obtained when increasing the ethylcellulose ratio up to 50%, indicating the enhanced solution compatibility due to the reduced intramolecular and intermolecular forces of gelatin and the increased entanglements among ethylcellulose and gelatin.…”
Section: Results and Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…The apparent viscosities of the EG01, EG13, EG11, EG31, and EG10 solutions were 2.51, 6.74, 5.24, 13.40, and 8.53 Pa s, respectively. When the weight ratio of ethylcellulose content was less than 50%, the viscosity of the blend was higher than that of the gelatin solution and lower than that of the ethylcellulose solution, indicating good compatibility on blending . Further, a minimum viscosity was obtained when increasing the ethylcellulose ratio up to 50%, indicating the enhanced solution compatibility due to the reduced intramolecular and intermolecular forces of gelatin and the increased entanglements among ethylcellulose and gelatin.…”
Section: Results and Discussionmentioning
confidence: 93%
“…When the weight ratio of ethylcellulose content was less than 50%, the viscosity of the blend was higher than that of the gelatin solution and lower than that of the ethylcellulose solution, indicating good compatibility on blending. 16 Further, a minimum viscosity was obtained when increasing the ethylcellulose ratio up to 50%, indicating the enhanced solution compatibility due to the reduced intramolecular and intermolecular forces of gelatin and the increased entanglements among ethylcellulose and gelatin. Ge et al reported that the reduced viscosity of the poly(n-butyl methacrylate) (PBMA)/polyacrylonitrile (PAN) systems with increasing PBMA content suggested good compatibility, due to the fact that the entry of PBMA molecules within the PAN threw apart the regularly arranged chains of PAN and broke up the molecular alignment to a certain extent.…”
Section: Journal Of Agricultural and Food Chemistrymentioning
confidence: 92%
See 2 more Smart Citations